PENGARUH GROWTH OPPORTUNITY DAN TAX SHIELD TERHADAP STRUKTUR MODAL DAN KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PADA PERIODE 2009-2012) - Famela Oktarina; Yulia Efni; Haryetti - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine the direct and indirect effect of growth opportunity and the tax shield that is mediated by the capital structure of the company's performance in the manufacturing sector of the consumer goods industry listed in Indonesia Stock Exchange (IDX) in the 2009-2012 period.The population in this study were 38 companies manufacturing consumer goods industry sector, and the sample used in this study were 27 companies with the number N of data as much as 104. The sample data collection technique is based on purposive sampling. Data analysis using descriptive analysis and path analysis.Based on the results of this study indicate that growth opportunity has a significant negative effect directly on the performance of the company, the tax shield has a significant influence directly on the performance of the company, capital structure has a significant negative effect directly on the performance of the company, growth opportunity does not have a significant effect on performance companies through direct capital structure and tax shield does not have a significant effect on the performance of the company through direct capital structure. This means that capital structure is not able to mediate the relationship between growth opportunity and the tax shield on the performance of the company.Keywords: Growth Opportunities, Tax Shield, Capital Structure and Company Performance.